2023
DOI: 10.3390/met13081494
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Nonlinear Lap Joint of 6061 Aluminum Alloy by Friction Stir Welding

Laipeng Qu,
Ning Ma,
Xiao Xiao
et al.

Abstract: The microstructure and properties of non-linear friction stir welded lap joints of the AA6061-T6 aluminum alloy were investigated, with a particular focus on the influence of corner curvature on the formability and mechanical properties of the joints. The research results indicate that for the 6061-T6 aluminum alloy lap joint friction stir welding with a smaller radius (R < 7 mm), there is a more severe accumulation of welding material. When the radius exceeds 7 mm, good macroscopic joint formation can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The study observed a curvature radius of less than 7 mm resulted in the accumulation of the welding material. A curvature radius of 7 mm was observed to be a critical value, as a decrease in this value resulted in poor joint performance and values above it resulted in better strength [123]. The researchers also evaluated the effect of pin eccentricity on weld joints for AA5754-H111 and AA6101-T6 alloys.…”
Section: Materials Combination and Process Optimization Developmentsmentioning
confidence: 99%
“…The study observed a curvature radius of less than 7 mm resulted in the accumulation of the welding material. A curvature radius of 7 mm was observed to be a critical value, as a decrease in this value resulted in poor joint performance and values above it resulted in better strength [123]. The researchers also evaluated the effect of pin eccentricity on weld joints for AA5754-H111 and AA6101-T6 alloys.…”
Section: Materials Combination and Process Optimization Developmentsmentioning
confidence: 99%